2017
DOI: 10.1177/0022429417728925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Listening Strategies for Melodic Dictation

Abstract: The purpose of this research was to examine effects of two listening strategies on melodic dictation scores. Fifty-four undergraduate music majors completed short tonal melodic dictations in a within-subjects design with three conditions: (a) no specified strategy in the instructions, (b) required listening before writing, and (c) required writing while listening. The purpose of the first condition was to determine subjects’ preference for listening before writing or writing while listening prior to requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
2
9
1
5
Order By: Relevance
“…Scores from participants’ demonstrated preferred strategy were not significantly higher than scores from their nonpreferred strategy, corroborating previous findings from a study of melodic dictation (Buonviri, 2017) and suggesting that students’ typical strategy may not necessarily be their best choice. Given the lack of a statistically significant difference in scores as a function of participants’ preferred strategy, the significant difference between writing while listening and listening before writing bears more weight.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Scores from participants’ demonstrated preferred strategy were not significantly higher than scores from their nonpreferred strategy, corroborating previous findings from a study of melodic dictation (Buonviri, 2017) and suggesting that students’ typical strategy may not necessarily be their best choice. Given the lack of a statistically significant difference in scores as a function of participants’ preferred strategy, the significant difference between writing while listening and listening before writing bears more weight.…”
Section: Discussionsupporting
confidence: 86%
“…Target rhythms were all two measures long, were in 4/4 meter, and incorporated combinations of quarter notes, eighth notes, sixteenth notes, and eighth rests (see Appendix S1 in the supplementary files included with the online version of this article for all target rhythms). In a previous study (Buonviri, 2017), two-measure melodies were effective for prompting students to choose which listening strategy to use, because they were long enough (10–12 notes each) to warrant some amount of sketching but short enough to commit to memory without sketching (Pembrook, 1986). In the current study, the use of sixteenth notes produced more notes per target than in Buonviri’s (2017) study, but I determined that the two-measure length would again be effective because the targets did not include pitch, serving to balance the increased number of notes in each.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a more recent study, Buonviri (in press) found that both strategies worked equally well for undergraduate music majors taking short tonal melodic dictations; his results corroborate Pembrook’s (1987) recommendation that both may be viable options.…”
Section: Resultsmentioning
confidence: 62%